Socio-demographic profile of Autism Spectrum Disorder: A Study in an Urban Area of Bangladesh (Journal of Dhaka National Medical College & Hospital, 2016)
This descriptive cross-sectional study was conducted to explore the socio-demographic profile of Autism Spectrum Disorder (ASD). The study was conducted for a period of six months from January to June 2015 and 'Institute for Paediatric Neuro-disorder and Autism' under BSMMU was considered as a place of study. Sample size was 111 ASD children and their parents were considered as respondent for interview. Frequency distributions of the selected socio-demographic factors were undertaken. Association of Socio-demographic profile with the different levels of disability (cognitive type) was tested by Bailey Scale of Infant Development. The mean age of the autistic child was 30.6 months (SD ± 6.855) .72.1% of them were male and 27.9% were female. More than seventy percent of them were first born child and all of them lived with their parents. About 70% mothers were educated. Educational status of the fathers were graduate and above 79 (71.2%) and 18 (16.2%) were limited within primary level. More than half of mothers (60.4%) of the child were housewives. Majority of fathers (86.5%) of autistic child were service holders. Most of the respondents had more than 4 family members. The mean monthly family income of the respondents was BDT 50,162.16 ± 37,747.857. 96 (86.5%) of the mothers delivered their first child at 25 years of age and below. In the present study more than seventy percent (70.7%) parents faced social problems and 29.3% parents suffered financial problems. In regard to intellectual disability, 85 (76.57%) children had significantly delayed performance level and 26 (23.42%) had mildly delayed performance level. There was no delayed performance in any children of this study group. The findings did not show any association of socio-demographic profile with the levels of intellectual disability. The result of this study gives emphasis for the need of further study in a larger scale with controls and larger sample size to obtain more information for planning and implementation.J. Dhaka National Med. Coll. Hos. 2016; 22 (01): 7-12